Performance of Tween 80 as Surfactant for Chitosan Drug Delivery Film - Nadya Alfa Imani; Maharani Kusumaningrum (CHEMICA: Jurnal Teknik Kimia, 2019)
Optimization of the drug delivery system is based on the need for more efficient and effective drugs to fight disease. The addition of surfactant as an additive in the drug delivery precursor solution can affect the performance of the material, especially on the ability of drug release. In this study, Tween 80 was used as a surfactant to be mixed in a low molecular weight chitosan solution. Several variations of the Tween 80: chitosan ratios, as well as variations in acidity conditions, are used to determine the optimum conditions for drug release. Drug release profile fittings were tested on three kinetic models that were frequently used namely zero order model, Higuchi’s model, and Korsmeyer-Peppa’s model. The results showed that the optimum conditions for release were obtained with the use of a ratio of 7:10 with a release profile resembling Korsmeyer-Peppa’s model.